Significant clinical presentation of leptospirosis in relation to socio-demographic and risk factors in a tertiary hospital, Malaysia - Mohd Taib, Niazlin; Ahmad, Hamidah; Soh, Kim Lam; Md Shah, Anim; Amin Nordin, Syafinaz; Lung, Leslie Than Thian; Abdullah, Maha; Chong, Chun Wie; Sekawi, Zamberi (Mary Ann Liebert, 2020)
Introduction: Incidence of leptospirosis has increased within the past few years in many countries. Its clinical presentations were generally nonspecific, making it difficult to assist in the diagnosis. Besides the determination of the common clinical features, the sociodemographic background is essential to identify high-risk populations to assist in prevention.